The Photoshop Elements 3 book for digital photographers - Kelby, Scott (New Riders/Peachpit, 2004)
If you're ready for an Elements 3 book that breaks all the rules, this is it, because it does something for digital photographers that's never been done before--it cuts through the bull and shows you exactly "how to do it." It tells you, flat-out, which settings to use, when to use them, and why. This book is not a bunch of theory; it doesn't challenge you to come up with your own settings or figure things out on your own. It gives you the same settings used by some of the top digital pros, settings you can use today to get professional results you've always dreamed of. Plus, since this book is designed for photographers, it doesn't waste your time talking about how to frame a shot, setting your exposure, etc. and there's no talk which camera or printer to buy. It's all Elements, step-by-step, cover-to-cover in the only book of its kind, and you¿re gonna love it! Besides learning the inside tips and the tricks of the trade for correcting, editing, sharpening, retouching, and presenting your photos like a pro. You'll learn how to unlock the power of all the new Elements 3 features, including how to manage your photos using the new Organizer, how to use the new "pro tools" like the Healing Brush and the Shadow/Highlight controls, and how to master the new "Creation" section to take your photos to an entirely new level. Plus, you'll see it all step-by-step, in plain English, and you¿ll be absolutely amazed at how easy and effective these techniques are, once you know the secrets. You'll learn: The secrets of how the pros retouch portraits How to incorporate the amazing new features of Elements 3 into your work today! How to color correct any photo without breaking a sweat (you¿ll be amazed at how they do it!) How to repair and restore damaged photos The sharpening techniques the pros really use (there's an entire chapter just on this!) Dealing with common digital camera image problems, including removing noise and avoiding halos When to use Quick Fix, and when to do to it yourself (using our step-by-step methods). The most-requested photographic special effects and much more! But besides all that, this book has a "secret weapon" that makes it the most important, most useful Elements book yet. The reason is this--although Elements 3 offers some digital photography features Photoshop CS doesn't offer, there are plenty of features that Photoshop CS has, that Elements 3 still doesn't have (things like Layer Masking, Channel Mixer, et cetera). But in this ...